Translucent ceramics, optical elements, and optical modulators
Patent Information
- Application Number
- JP2025059928
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166761000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to translucent ceramics.
Background Art
[0002] As materials used for optical components such as optical modulators, single crystals are often used because translucency is required. As one of the candidate materials, for example, Patent Document 1 proposes an alkali niobate / tantalate perovskite-type oxide.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] The production of single crystals, due to its production process, may increase production costs, cause difficulties in mass production, and pose problems such as upsizing. Therefore, there is a demand for a technology that can easily produce translucent materials used for optical components.
Means for Solving the Problems
[0005] The present disclosure can be implemented in the following modes.
[0006] (1) According to one aspect of the present disclosure, a translucent ceramic is provided. This translucent ceramic includes a main phase composed of an alkali niobate / tantalate perovskite-type oxide, and a secondary phase composed of a spinel compound containing Ti, has a thickness of 500 μm or less, and is characterized in that the maximum value of the total transmittance for light in the wavelength region of 190 nm or more and 1100 nm or less is 20% or more. According to the translucent ceramic of this aspect, production of a translucent material used for optical components can be performed easily.
[0007] (2) In the translucent ceramic described in (1) above, the spinel compound may be an M-Ti-O based spinel compound, the element M is a 1 to 4 valent element, and may include at least one metal element selected from Li, Mg, Al, Sc, Cr, Mn, Fe, Co, Ni, Zn, Ga, Y, and Zr. According to the translucent ceramic of this aspect, the translucency can be further improved.
[0008] (3) In the translucent ceramic described in (2) above, the M-Ti-O based spinel compound has a compositional formula M x TiO y , where the coefficients x and y are relative values when the Ti content is set to 1, the coefficient x may satisfy 0.5≦x≦5.0, and the coefficient y may satisfy 2.0≦y≦8.0. According to the translucent ceramic of this aspect, the translucency can be further improved.
[0009] (4) In the translucent ceramic according to any one of (1) to (3) above, the alkali niobate / tantalate perovskite-type oxide has a compositional formula (K a Na b Li c C d ) e (D f E g )O his represented by, element C is one or more of Ca, Sr, and Ba, element D is one or more of Nb, Ta, Ti, Zr, Hf, Sn, Sb, and Si that includes at least Nb or Ta, element E is one or more of Mg, Al, Sc, Mn, Fe, Co, Ni, Zn, Ga, and Y, and satisfies 0<a<1, 0<b<1, 0≦c<1, 0≦d<0.5, 0<f<1, 0≦g<0.5, 0.80≦e≦1.10, and h may be any arbitrary value that constitutes a perovskite. According to the translucent ceramics of this embodiment, the translucency can be further improved.
[0010] (5) According to another embodiment of the present disclosure, there is provided an optical element comprising the translucent ceramics according to any one of the above (1) to (4), and an electrode. According to the optical element of this embodiment, complication of the manufacturing process can be suppressed.
[0011] (6) According to another embodiment of the present disclosure, there is provided an optical modulator comprising the translucent ceramics according to any one of the above (1) to (4). According to the optical modulator of this embodiment, complication of the manufacturing process can be suppressed.
[0012] Note that the present disclosure can be implemented in various forms, for example, in forms such as a method for producing translucent ceramics, a method for producing an optical element including translucent ceramics, a method for producing an optical modulator including translucent ceramics, use of translucent ceramics as an optical element, use of translucent ceramics as an optical modulator, use of translucent ceramics for manufacturing an optical element, and use of translucent ceramics for manufacturing an optical modulator. [Brief Description of the Drawings]
[0013] [Figure 1] It is a perspective view schematically showing the schematic configuration of an optical element. [Figure 2] It is a perspective view schematically showing an example of the schematic configuration of an optical modulator. [Modes for Carrying Out the Invention]
[0014] A translucent ceramic as one embodiment of the present disclosure comprises a main phase made of a niobium / alkali tantalate perovskite-type oxide and a secondary phase made of a spinel compound containing Ti (titanium), has a thickness of 500 μm or less, and has a maximum total transmittance of 20% or more in the wavelength region of 190 nm to 1100 nm. From the viewpoint of improving translucency, the thickness of the translucent ceramic is preferably 100 μm or less, and more preferably 30 μm or less. The wavelength region of 190 nm to 1100 nm corresponds to the wavelength region from visible light to near-infrared light. In this disclosure, "maximum total transmittance" means the maximum total transmittance among the total transmittances of light at each wavelength. The transmittance is calculated by analysis using ultraviolet-visible spectroscopy. More specifically, ultraviolet-visible spectroscopy is performed using an integrating sphere under the following measurement conditions: measurement wavelength: 190 nm to 1100 nm, scan speed: 1200 nm / min, integration time: 0.05 sec, and data interval: 1 nm. The maximum total transmittance among the total transmittances obtained at each wavelength can then be calculated as the maximum value of total transmittance (%).
[0015] In this disclosure, "main phase" means the first crystalline phase that forms the translucent ceramic, and "secondary phase" means the second crystalline phase that forms the translucent ceramic. The proportion of the main phase in the translucent ceramic is 85% by volume or more and less than 100% by volume, and the proportion of the secondary phase in the translucent ceramic is greater than 0% by volume and 15% by volume or less. As will be described later, the translucent ceramic may contain crystalline phases other than the main phase and the secondary phase.
[0016] The perovskite oxide forming the main phase preferably contains at least one of an alkali niobate-based perovskite oxide and an alkali tantalate-based perovskite oxide. The term "alkali niobate / tantalate-based perovskite oxide" is a general term for these multiple types of perovskite oxides. The alkali-based component of the alkali niobate / tantalate-based perovskite oxide contains at least an alkali metal, and may also contain an alkaline earth metal. The alkali metal is not particularly limited, and examples thereof include K (potassium), Na (sodium), Li (lithium) and the like. The alkaline earth metal is not particularly limited, and examples thereof include Ca (calcium), Sr (strontium), Ba (barium) and the like. From the viewpoint of improving translucency, such an alkali niobate / tantalate-based perovskite oxide is preferably represented by the following composition formula (1).
[0017] (K a Na b Li c C d ) e (D f E g )O h ···(1) Here, element C is one or more of Ca (calcium), Sr (strontium), and Ba (barium), element D is one or more containing at least Nb or Ta among Nb (niobium), Ta (tantalum), Ti (titanium), Zr (zirconium), Hf (hafnium), Sn (tin), Sb (antimony), and Si (silicon), element E is one or more of Mg (magnesium), Al (aluminum), Sc (scandium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zn (zinc), Ga (gallium), and Y (yttrium), satisfying 0<a<1, 0<b<1, 0≦c<1, 0≦d<0.5, 0<f<1, 0≦g<0.5, 0.80≦e≦1.10, and h is an arbitrary value constituting the perovskite structure,
[0018] In the above compositional formula (1), when element C may contain 1 to 2 elements, and each of element D and element E may contain 1 to 3 elements, it can be rewritten as the following compositional formula (1a).
[0019] (K a Na b Li c C1 d1 C2 d2 ) e (D1 f1 D2 f2 D3 f3 E1 g1 E2 g2 E3 g3 )O h ···(1a) Here, 0<a<1, 0<b<1, 0≦c<1, 0≦(d1+d2)<0.5, 0<(f1+f2+f3)<1, 0≦(g1+g2+g3)<0.5, 0.80≦e≦1.10 are satisfied, and h is an arbitrary value that constitutes the perovskite. This compositional formula (1a) is equivalent to the above compositional formula (1). As can be understood from this example, when element C includes two types of metal elements, the value of the coefficient d of element C is represented by the sum of the coefficients d1 and d2 of the two types of elements C1 and C2. When element D includes three types of metal elements, the value of the coefficient f of element D is represented by the sum of the coefficients f1, f2, and f3 of the three types of elements D1, D2, and D3. The same applies to, for example, cases where element D includes four or more types of metal elements.
[0020] In the above compositional formula (1), K (potassium), Na (sodium), Li (lithium), and element C (Ca, Sr, Ba) are located at the so-called A site of the perovskite structure. Element D (at least one of Nb, Ta, Ti, Zr, Hf, Sn, Sb, Si, including at least Nb or Ta) and element E (at least one of Mg, Al, Sc, Mn, Fe, Co, Ni, Zn, Ga, Y) are located at the so-called B site of the perovskite structure. Of the coefficients a, b, c, and d for the elements at the A site, coefficients c and d may be zero. Also, of the coefficients f and g for elements D and E at the B site, coefficient g for element E may be zero. In other words, the niobium / alkali tantalate perovskite oxide of this embodiment is preferably a perovskite oxide that contains at least one alkali metal (K, Na, Li) and may contain alkaline earth metals (Ca, Sr, Ba) at its A site, and at least one of Nb or Ta from among Nb, Ta, Ti, Zr, Hf, Sn, Sb, and Si and may contain one or more other metals (Mg, Al, Sc, Mn, Fe, Co, Ni, Zn, Ga, Y) at its B site. Furthermore, the B site most preferably contains Nb. An alkali niobate perovskite oxide containing Nb is preferable to an alkali tantalate perovskite oxide that does not contain Nb in that it has a higher phase transition temperature and can provide a translucent ceramic with a wider practical temperature range.
[0021] As the values of the coefficients a, b, c, d, e, f, g, and h in the above compositional formula (1), values preferable from the viewpoint of the electrical characteristics or piezoelectric characteristics (particularly the piezoelectric constant d33) of the translucent ceramics can be selected from combinations of values that allow the perovskite structure to be established. Specifically, the coefficients a and b of K and Na are preferably 0 < a ≤ 0.6 and 0 < b ≤ 0.6. The coefficient c of Li may be zero, but is preferably 0 < c ≤ 0.2, and more preferably 0 < c ≤ 0.1. The coefficient d of element C (one or more of Ca, Sr, and Ba) may be zero, but is preferably 0 < d ≤ 0.2, and more preferably 0 < d ≤ 0.1. The coefficient e for the entire A-site is preferably 0.84 ≤ e ≤ 1.08, and more preferably 0.88 ≤ e ≤ 1.07. The coefficient h of oxygen can take any value such that the main phase constitutes a perovskite oxide. A typical value of the coefficient h is about 3, and is preferably 3.0 ≤ h ≤ 3.1. The value of the coefficient h can be calculated from the electrical neutrality condition of the composition of the main phase. However, as the composition of the main phase, a composition slightly deviating from the electrical neutrality condition is also permissible. In addition, the alkali niobate / tantalate perovskite oxide according to the present embodiment may contain other elements as necessary.
[0022] A typical composition of the main phase is (K, Na, Li, Ca, Ba) e (Nb, Ti, Zr)O h , which contains K, Na, and Nb as the main metal components. Since this main phase contains K, Na, and Nb as the main metal components, the material composed of the main phase is also referred to as "KNN" or "KNN material", and the main phase is also referred to as "KNN phase".
[0023] The spinel compound forming the subphase contains Ti (titanium). In this disclosure, "spinel compound" includes both positive spinel compounds having a positive spinel crystal structure and inverse spinel compounds having an inverse spinel crystal structure. As a spinel compound containing Ti, it is preferable that it is an M-Ti-O system spinel compound from the viewpoint of improving light transmittance. Here, element M is a 1- to 4-valent metallic element. Element M is preferably at least one metallic element from among Li (lithium), Mg (magnesium), Al (aluminum), Sc (scandium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Zn (zinc), Ga (gallium), Y (yttrium), and Zr (zirconium). As such an M-Ti-O system spinel compound, it is preferable that it is represented by the following compositional formula (2) from the viewpoint of improving light transmittance.
[0024] M x TiO y ...(2) Here, element M is a 1-4 valent metallic element, and includes at least one metallic element from Li, Mg, Al, Sc, Cr, Mn, Fe, Co, Ni, Zn, Ga, Y, and Zr, where the coefficients x and y are relative values when the Ti content is set to 1. It is preferable that the coefficient x satisfies 0.5 ≤ x ≤ 5.0. The coefficient y is any value that forms the spinel compound, but it is preferable that it satisfies 2.0 ≤ y ≤ 8.0. When element M includes Li, it is preferable that one or more metallic elements other than Li from the above metallic elements are included together with Li in order for the subphase to form the spinel compound. The subphase composed of the spinel compound promotes the densification of the entire sample, so that a translucent ceramic with excellent light transmission can be obtained. From the viewpoint of light transmission, it is preferable that the subphase is represented by the composition formula M2TiO4 or (M1,M2)TiO4, which includes two divalent metallic elements M.
[0025] Note that the compositional formulas of the various spinel compounds described above are not strictly defined, and the compositional formulas obtained from actual analysis may differ slightly. However, the compositional formula obtained from analysis may also differ from the compositional formula (M) shown in equation (2) above.x TiO y The fact that it satisfies the requirements remains unchanged, and it is common in that it is a compositional formula that represents a titanate compound having a spinel structure. Furthermore, the spinel compound according to this embodiment may contain other elements as needed.
[0026] The spinel compound forming the secondary phase may be either a positive spinel compound or an inverse spinel compound. Whether or not the secondary phase is a spinel compound can be determined by Rietveld analysis using the diffraction results of powder X-ray diffraction (XRD). Analysis of the amount of metal elements other than Li in the spinel compound can be performed using electron beam microanalyzer (EPMA) or energy-dispersive X-ray spectroscopy (TEM-EDS). Furthermore, the amount of Li can be analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS).
[0027] The secondary phase, by being mixed with the primary phase, improves the sinterability of translucent ceramics, enhances their structural stability, and improves their translucency. Specifically, the secondary phase fills the voids formed between the fine crystals of the primary phase. As a result, the fine crystals of the primary phase are bonded together by the secondary phase, which is presumed to improve the structural stability and translucency of the translucent ceramics.
[0028] From the viewpoint of the translucency of translucent ceramics, the proportion of the subphase contained in the translucent ceramics is preferably 0.1 volume% to 15.0 volume%, more preferably 0.5 volume% to 10.0 volume%, and even more preferably 1.0 volume% to 5.0 volume%.
[0029] Translucent ceramics may contain crystalline phases other than the main phase and secondary phases (such as a third crystalline phase). For example, A3B5O 15 It is preferable to use the crystalline phase of a compound system (element A is a 1-2 valent metal, element B is a 2-5 valent metal). A3B5O 15As a system compound, a compound can be used in which element A (a metal with 1-2 valencies) is at least one of Ba, Ca, Sr, Na, K, and Li, and element B (a metal with 2-5 valencies) is at least one of Nb, Mn, Fe, Ni, Co, Zn, and Zr. Specifically, for example, (Ba,Na,K)3(Nb,Ni,Fe)5O 15 (Ba,Na,K)3(Nb,Co,Ni)5O 15 (Ba,Na,K)3(Nb,Zn)5O 15 (Ba,Na,K)3(Nb,Mn)5O 15 (Ba,Na,K)3(Nb,Fe,Zn,Co)5O 15 It is possible to utilize such a third crystalline phase. When such a third crystalline phase is present, the spinel compound of the secondary phase becomes less susceptible to alteration, and the spinel compound is stabilized, which is presumed to improve the overall stability of the translucent ceramic. When the translucent ceramic further contains a third crystalline phase, etc., the volume ratio of the second crystalline phase, when the total crystalline phase including the second and third crystalline phases is taken as 100%, is preferably 50% or more, more preferably 70% or more, and even more preferably 80% or more. The reason for this is to prevent the effect of the second crystalline phase in stabilizing the structure of the first crystalline phase from becoming insufficient due to a decrease in the proportion of the second crystalline phase. When the translucent ceramic contains a crystalline phase other than the main phase and secondary phase (such as a third crystalline phase), the third crystalline phase, etc., fills the voids formed between the fine crystals of the main phase, similar to the secondary phase.
[0030] An example of a method for producing the translucent ceramics of this disclosure is described below. First, the main phase raw materials are mixed. In this case, the necessary raw materials for the main phase are selected from among raw materials such as K2CO3 powder, Na2CO3 powder, Li2CO3 powder, CaCO3 powder, SrCO3 powder, BaCO3 powder, Nb2O5 powder, Ta2O5 powder, TiO2 powder, ZrO2 powder, MgO powder, Al2O3 powder, Sc2O3 powder, MnO2 powder, Fe2O3 powder, CoO powder, NiO powder, ZnO powder, Ga2O3 powder, and Y2O3 powder, and weighed according to the values of the coefficients a, b, c, d, e, f, and g in the composition formula of the main phase. Then, ethanol is added to these raw material powders and wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. Next, the slurry is dried to obtain a mixed powder, which is then calcined, for example, under atmospheric conditions at a temperature of 600°C to 1100°C for 1 to 10 hours to produce the main phase calcined powder.
[0031] Separately, the raw materials for the secondary phase are mixed. In this process, in addition to TiO2 powder, the necessary raw materials for the secondary phase are selected from Li2CO3 powder, MgO powder, Al2O3 powder, Sc2O3 powder, Cr2O3 powder, MnO2 powder, Fe2O3 powder, CoO powder, NiO powder, ZnO powder, Ga2O3 powder, Y2O3 powder, ZrO2 powder, etc., and weighed according to the value of the coefficient x in the composition formula of the secondary phase. Then, ethanol is added to these raw material powders and wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. Next, the slurry is dried and the resulting mixed powder is calcined, for example, under an atmospheric environment at a temperature of 600°C to 1100°C for 1 to 10 hours to produce secondary phase calcined powder. This secondary phase calcined powder is a powder of a spinel compound or a precursor of a spinel compound. The precursor of the spinel compound is not a spinel compound at the end of this calcination stage, but becomes a spinel compound through the calcination process described later. Note that the third crystalline phase (for example, A3B5O) 15 When producing translucent ceramics further containing (system compounds), metal oxide powder, which will be the raw material for the third crystalline phase, may be appropriately mixed when mixing the raw materials for the secondary phase or when generating the secondary phase calcined powder.
[0032] Next, the main phase calcined powder and the secondary phase calcined powder are weighed separately, and a dispersant, binder, and ethanol are added to them in a ball mill, then they are ground and mixed to obtain a slurry. Furthermore, the mixture obtained by drying this slurry is calcined for 1 to 10 hours at a temperature of 600°C to 1100°C under an atmospheric environment, for example, to produce calcined powder. The preferred content of the secondary phase in translucent ceramics is specified in volume percent, and the mixing ratio of the main phase calcined powder and the secondary phase calcined powder may be determined based on the mass of the main phase calcined powder and the secondary phase calcined powder. In this case, the relationship between the proportion of the secondary phase (mass %) at the time of mixing and the proportion of the secondary phase (volume %) in the final translucent ceramics can be determined empirically in advance.
[0033] The obtained calcined powder is again mixed with a dispersant, binder, and ethanol to obtain a slurry. Furthermore, this slurry is dried in a spray dryer, granulated, and molded to the desired thickness and shape by, for example, uniaxial pressing at a pressure of 20 MPa. After that, a molded body is obtained by performing CIP (cold isohydrostatic pressing) at a pressure of 150 MPa, for example. The obtained molded body is held at, for example, 500°C to 800°C in an atmospheric environment for 2 to 10 hours to degrease the binder. Translucent ceramics are obtained by firing the degreased molded body at, for example, a specific temperature selected from 1000°C to 1300°C (e.g., 1150°C) for 2 to 50 hours in an atmospheric environment. This firing is preferably a sealed firing, where the molded body is sealed in a sealed container. This is to prevent metallic elements such as alkali metals (Li, Na, K) contained in the molded body from disappearing to the outside during firing. As such a sealed container, for example, an alumina scabbard A-1174 manufactured by Otake Ceram Co., Ltd. can be used. Furthermore, after polishing the sample obtained by firing to a predetermined thickness using a fully automatic rotary surface grinder (Sanshin Seiki Co., Ltd., SPG-300 CNC), the surface was polished by first using #1000 waterproof abrasive paper, then #2000 waterproof abrasive paper, followed by buff polishing with a 1 μm diamond abrasive to finish the surface. It is believed that by performing the surface treatment as described above, stably translucent properties can be achieved. Thus, translucent ceramics can be manufactured.
[0034] The above manufacturing method is merely one example, and various other processes and processing conditions can be used to produce translucent ceramics. For example, instead of separately producing the main phase and sub-phase beforehand and then mixing and firing the powders of both, the translucent ceramics may be produced by mixing the raw materials in a quantity ratio corresponding to the final composition of the translucent ceramics and then firing them. Furthermore, by separately producing the main phase and sub-phase beforehand, it is easier to more precisely control the composition of the main phase and sub-phase, thereby increasing the yield of translucent ceramics.
[0035] Figure 1 is a schematic perspective view showing an example of the schematic configuration of an optical element 10 as another embodiment of the present disclosure. According to another embodiment of the present disclosure, an optical element 10 is provided. This optical element 10 includes the translucent ceramic 20 described above and an electrode 30. According to this embodiment of the optical element 10, the complexity of the manufacturing process can be suppressed.
[0036] The translucent ceramic 20 has a roughly rectangular, thin plate-like appearance and a thickness of 500 μm or less. From the viewpoint of improving light transmission, the thickness of the translucent ceramic 20 is preferably 100 μm or less, and more preferably 30 μm or less. The electrode 30 is formed by a pair of electrodes provided at both ends of the translucent ceramic 20. The material for forming the electrode 30 is not particularly limited, but examples include Ti (titanium), Ni (nickel), Cu (copper), Pt (platinum), Ag (silver), Pd (palladium), etc., and alloys thereof. When an electric field is applied to the translucent ceramic 20 by applying a voltage to the electrode 30, the refractive index of the translucent ceramic 20 changes. As a result, light such as a laser is transmitted through the translucent ceramic 20 and its wavelength is converted. The form of the optical element 10 shown in Figure 1 is merely an example, and can be applied to various parts and devices such as optical scanners and variable focus lenses.
[0037] Figure 2 is a schematic perspective view showing an example of the schematic configuration of an optical modulator 40 as another embodiment of the present disclosure. According to another embodiment of the present disclosure, an optical modulator 40 is provided, which includes the translucent ceramic 20 described above. According to this embodiment of the optical modulator 40, the complexity of the manufacturing process can be suppressed. The optical modulator 40 shown in Figure 2 further includes a conductive film 50 and a conductor 60.
[0038] The translucent ceramic 20 has a roughly rectangular parallelepiped shape and is formed with a thickness of 500 μm or less along the optical axis X. The conductive film 50 is provided on both sides of the translucent ceramic 20 where positive and negative surface charges are generated. The material for forming the conductive film 50 is not particularly limited as long as it has conductivity sufficient to remove surface charges, and examples include inorganic conductive materials such as silver, carbon, gold, and silver-palladium, and organic conductive materials such as polyaniline. The method for forming the conductive film 50 is not particularly limited, but examples include forming it by applying a conductive paste to the translucent ceramic 20, forming it by depositing a conductive substance, and forming it by sputtering. The two conductive films 50 are connected to each other and short-circuited by a conductor 60. The conductive film 50 and the conductor 60 are provided so as to ensure conductivity on the surfaces where positive and negative charges are generated without obstructing the optical path along the optical axis X, and are provided in accordance with the crystal cutting angle, shape, etc. Furthermore, there are no particular restrictions on the structure and arrangement of the conductive film 50 and the conductor 60, and any configuration that can remove the charge generated on the crystal surface of the translucent ceramic 20 is acceptable.
[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0040] 1. Sample Samples of translucent ceramics for the comparative example and samples of translucent ceramics for the example were prepared. The translucent ceramics of the comparative example contain only the main phase and no secondary phases. In preparing the comparative example sample, first, K2CO3 powder, Na2CO3 powder, BaCO3 powder, CaCO3 powder, Nb2O5 powder, TiO2 powder, and ZrO2 powder were used as raw materials for the main phase, and the composition formula of the main phase ((K a Na b Li c C d ) e (D f E g )O hIn this experiment, elements C were weighed out such that Ba (coefficient d1) and Ca (coefficient d2), elements D were Nb (coefficient f1), Ti (coefficient f2), and Zr (coefficient f3), and coefficients a to g were a=0.46, b=0.46, c=0, d1=0.04, d2=0.04, e=1.00, f1=0.92, f2=0.04, f3=0.04, and g=0. Ethanol was added to these powders and wet-mixed in a ball mill for 15 hours to obtain a slurry. The slurry was then dried and the resulting mixed powder was calcined in an air atmosphere at 600°C to 1100°C for 1 to 10 hours to obtain a calcined product. This calcined product was then pulverized and mixed in a ball mill with a dispersant, binder, and ethanol to obtain a slurry. The slurry was then dried, granulated, and formed into a square shape with sides of approximately 20 mm by uniaxial pressing at a pressure of 20 MPa. Subsequently, a CIP treatment was performed at a pressure of 150 MPa, and the resulting CIP-pressed body was degreased and then fired at 1180°C for 5 hours in an atmospheric environment.
[0041] The translucent ceramics of the examples include both a main phase and a secondary phase. The composition of the main phase in the translucent ceramics of the examples was the same as that of the main phase in the translucent ceramics of the comparative example. The composition of the secondary phase in the translucent ceramics of the examples is shown in Table 1 below.
[0042] In preparing the samples for the examples, first, as with the comparative example, K2CO3 powder, Na2CO3 powder, BaCO3 powder, CaCO3 powder, Nb2O5 powder, TiO2 powder, and ZrO2 powder were used as raw materials for the main phase, and the composition formula of the main phase was ((K a Na b Li c C d ) e (D f E g )O hIn the following experiment, elements C was weighed out as Ba (coefficient d1) and Ca (coefficient d2), elements D as Nb (coefficient f1), Ti (coefficient f2) and Zr (coefficient f3), and coefficients a to g were weighed out such that a=0.46, b=0.46, c=0, d1=0.04, d2=0.04, e=1.00, f1=0.92, f2=0.04, f3=0.04, and g=0. Ethanol was added to these powders and wet-mixed in a ball mill for 15 hours to obtain a slurry. The slurry was then dried and the resulting mixed powder was calcined in an air atmosphere at 600°C to 1100°C for 1 to 10 hours to obtain the main phase calcined product. In addition, as raw materials for the secondary phase, necessary materials were selected from among TiO2 powder, Li2CO3 powder, MgO powder, Al2O3 powder, Sc2O3 powder, Cr2O3 powder, MnO2 powder, Fe2O3 powder, CoO powder, NiO powder, ZnO powder, Ga2O3 powder, Y2O3 powder, ZrO2 powder, etc., and weighed according to the coefficient values in the composition formula of the secondary phase M-Ti-O spinel compound listed in Table 1 below. Ethanol was added to these powders and wet-mixed in a ball mill for 15 hours to obtain a slurry. The slurry was then dried and the resulting mixed powder was calcined in an air atmosphere at 600°C to 1100°C for 1 to 10 hours to obtain the secondary phase calcined powder. Next, the main phase calcined powder and the secondary phase calcined powder were weighed separately and ground and mixed in a ball mill with a dispersant, binder, and ethanol to obtain a slurry. Subsequently, the slurry was dried, granulated, and formed into a square shape with sides of approximately 20 mm by uniaxial pressing at a pressure of 20 MPa. The thickness of each sample was as shown in Table 1 below (μm). Then, a CIP treatment was performed at a pressure of 150 MPa, and the resulting CIP-pressed body was degreased and then fired at 1180°C for 5 hours in an air atmosphere. The fired samples were polished using a fully automatic rotary surface grinder (Sanshin Seiki Co., Ltd., SPG-300 CNC). After polishing, at least the surfaces into which light was incident and emitted were polished with #1000 waterproof abrasive paper, then #2000 waterproof abrasive paper, and finally buffed with a 1 μm diamond abrasive to achieve the thickness shown in Table 1. In all of the translucent ceramic samples in the examples, the proportion of the main phase was 98 volume% and the proportion of the secondary phase was 2 volume%.
[0043] 2.Transmittance The transmittance of the comparative example and example samples was determined in the wavelength range from visible light to near-infrared light. The transmittance was calculated by analysis using ultraviolet-visible spectroscopy. Measurements were performed using an ultraviolet-visible near-infrared spectrophotometer (V-570, JASCO Corporation) under the following conditions: measurement wavelength: 190 nm to 1100 nm, scan speed: 1200 nm / min, integration time: 0.05 sec, and data interval: 1 nm. In addition, to reduce noise in the measurement data, an 11-term moving average was calculated for the total transmittance data for each wavelength. The maximum total transmittance (%) obtained among the total transmittances of light at each wavelength was calculated as the maximum value of the total transmittance.
[0044] 3.Results The results are shown in Table 1 below.
[0045] [Table 1]
[0046] As shown in Table 1, the sample of Comparative Example 1 had a maximum total transmittance of less than 10% in the wavelength range from 190 nm to 1100 nm. Therefore, the sample of Comparative Example 1 was suggested to be inferior from the viewpoint of optical applications due to insufficient light transmission. In contrast, the samples of Examples 1 to 13 all had a maximum total transmittance of 20% or more in the wavelength range from 190 nm to 1100 nm. Therefore, the samples of Examples 1 to 13 were suggested to be superior from the viewpoint of optical applications due to their excellent light transmission.
[0047] The present invention is not limited to the embodiments described above, and can be realized in various configurations without departing from its spirit. For example, the technical features in the embodiments and examples corresponding to the technical features in each form described in the summary of the invention can be replaced or combined as appropriate in order to solve some or all of the above-described problems, or to achieve some or all of the above-described effects. Furthermore, if a technical feature is not described as essential in this specification, it can be deleted as appropriate. [Explanation of Symbols]
[0048] 10…Optical element, 20…Transparent ceramics, 30…Electrode, 40…Optical modulator, 50…Conductive film, 60…Conducting wire, X…Optical axis
Claims
1. Translucent ceramics, The main phase consists of a niobium / alkali tantalate perovskite-type oxide, A subphase consisting of a spinel compound containing Ti, Includes, The thickness is 500 μm or less. The maximum total transmittance in the wavelength range of 190 nm to 1100 nm is 20% or more. A translucent ceramic characterized by the following features.
2. In the translucent ceramics according to claim 1, The aforementioned spinel compound is an M-Ti-O type spinel compound, Element M is a 1-4 valent element and includes at least one metallic element from among Li, Mg, Al, Sc, Cr, Mn, Fe, Co, Ni, Zn, Ga, Y, and Zr. A translucent ceramic characterized by the following features.
3. In the translucent ceramics according to claim 2, The aforementioned M-Ti-O spinel compound has the compositional formula M x TiO y It is represented as, The coefficients x and y are relative values when the Ti content is set to 1. The coefficient x satisfies 0.5 ≤ x ≤ 5.0, The coefficient y satisfies 2.0 ≤ y ≤ 8.
0. A translucent ceramic characterized by the following features.
4. In the translucent ceramics according to claim 1, The alkali niobate / tantalate perovskite-type oxide is represented by the composition formula (K a Na b Li c C d ) e (D f E g )O h , and Element C is one or more of Ca, Sr, and Ba. Element D is one or more of the following: Nb, Ta, Ti, Zr, Hf, Sn, Sb, Si, which includes at least Nb or Ta. Element E is one or more of the following: Mg, Al, Sc, Mn, Fe, Co, Ni, Zn, Ga, Y. The following conditions are satisfied: 0 < a < 1, 0 < b < 1, 0 ≤ c < 1, 0 ≤ d < 0.5, 0 < f < 1, 0 ≤ g < 0.5, 0.80 ≤ e ≤ 1.10, where h is any value that constitutes the perovskite. A translucent ceramic characterized by the following features.
5. A translucent ceramic according to any one of claims 1 to 4, Electrodes and, Optical elements, including those mentioned above.
6. A translucent ceramic comprising the translucent ceramic described in any one of claims 1 to 4, Optical modulator.
Citation Information
Patent Citations
Method for producing single crystal of potassium niobate
JP3397839B2